Report on the International Management Teachers Academy (IMTA) held in Bled, June 15–21, 2025 - Fábics, István (Public Finance Quarterly, 2025)
Between June 15–21, 2025, the renowned IMTA (International Management Teachers Academy) program took place in Bled, Slovenia, organized by CEEMAN (Central and East European Management Development Association). The program’s objective was to prepare participants for the application of modern, student-centered, and experience-based teaching methods, with particular emphasis on case study–based instruction, which plays a deﬁning role in international business and management education.